The Effect of Using Group Chat Discussion on Whatsapp Into Students’ Vocabulary Mastery Seventh Grade at SMP St Yoseph Medan - Bintang Hana Pardede; Sahlan Tampubolon; Febrika Dwi Lestari (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study focuses on kowing the effect of using group chat discussion on whatsapp into student’s vocabulary mastery seventh grade at SMP St Yoseph Medan. This research used experimental quantitative. The population of this study were seventh grade at SMP St Yoseph Medan. This research was conducted with two groups of purposive sampling, namely the experimental class and the control class. The data were collected using the vocabulary test. Data collection is done by giving a test. The test used were pre-test and post-test for both classes. The average score of pre-test in the experimental class is 60 and score of post-test in the experimental class is 79. The average pre-test score of pre-test in the control class is 55 and score of post-test in the control class is 73. The data were analyzed by using the T-test. The results of the calculation show that t count (0,80) is greater than t table (a) 0,03 with degrees of freedom df (57). This means that there was a significant influence of use group chat discussion on whatsapp into student’s vocabulary mastery. So, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The result of the study showed that by using whatsApp group chat, the students could improve significantly on vocabulary mastery. Keywords: Group Chat Discussion, WhatsApp, Student’s Vocabulary Mastery.